1990
DOI: 10.1029/ja095ia08p12157
|View full text |Cite
|
Sign up to set email alerts
|

High‐resolution sounding rocket observations of large‐amplitude Alfvén waves

Abstract: Shear Alfvén waves with amplitudes >100 mV/m were observed on two recent sounding rocket flights: one flown from Poker Flat, Alaska, to an altitude of 1040 km in the evening auroral zone, and another flown from Sondre Stromfjord, Greenland, to an altitude of 770 km in the morning cusp region. The largest waveforms are best described as a series of step functions, rather than as broadband noise or as single frequency waves. Complete two‐dimensional E and B measurements at 4‐ms time resolution were made, showing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
73
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(79 citation statements)
references
References 25 publications
6
73
0
Order By: Relevance
“…If n 0 8000 cm À3 then v e 2679 km s À1 and R e 0X3 mho; if n 0 4000 cm À3 then v e 3788 km s À1 and R e 0X21 mho; and if n 0 2000 cm À3 then v e 5358 km s À1 and R e 0X15 mho. All these values of density are consistent with various models and observations of the auroral ionosphere (e.g., Maeda, 1975;Boehm et al, 1990). In all three cases the value of R e is much smaller than the value of R and, therefore, typically % À1 at the ionosphere.…”
Section: Finite Ionospheric Conductivity Modelsupporting
confidence: 74%
“…If n 0 8000 cm À3 then v e 2679 km s À1 and R e 0X3 mho; if n 0 4000 cm À3 then v e 3788 km s À1 and R e 0X21 mho; and if n 0 2000 cm À3 then v e 5358 km s À1 and R e 0X15 mho. All these values of density are consistent with various models and observations of the auroral ionosphere (e.g., Maeda, 1975;Boehm et al, 1990). In all three cases the value of R e is much smaller than the value of R and, therefore, typically % À1 at the ionosphere.…”
Section: Finite Ionospheric Conductivity Modelsupporting
confidence: 74%
“…A close correlation of auroral whistler waves and auroral Alfvén waves was reported by Gustafsson et al (1990). In particular, simultaneous detection of whistler, Alfvén and Lagnmuir waves propagating along the auroral magnetic field lines was reported by Boehm et al (1990), in connection with an intense flux of field-aligned electrons. The aforementioned observations render support for nonlinear interactions of whistler, Langmuir and Alfvén waves in space environment.…”
Section: Discussionmentioning
confidence: 86%
“…Recently, we have shown that the nonlinear coupling of Langmuir waves with low-frequency magnetic field fluctuations, such as Alfvén waves, may also provide an efficient mechanism for generating magnetospheric radio waves (Chian et al, 1994;Lopes and Chian, 1996a;Chian et al, 2000). Evidence of this emission mechanism has been obtained in rocket experiments in the Earth's auroral plasmas (Boehm et al, 1990;Chian et al, 1994). In this paper, we present a nonlinear…”
Section: Introductionmentioning
confidence: 92%
“…100 km at the ionosphere's height , while the ESs are related to weaker pronounced 'holes'. One can also see that the cavities (Mozer et al, 1977;Persoon et al, 1988;Hultqvist, 1991) Small-Scale Anti-Parallel Field-Aligned Currents and Plasma Density Dips S45 been reported (Boehm et al, 1990) and (Abe et al, 1993). The width of the deepest, A = n /ndip -1 -10, `dip' is of the order of A l <-500 m. In its neighbourhood there are several moderately depleted `holes', A.2 <-(5-10)x,1.…”
Section: On Plasma Density Reductionsmentioning
confidence: 94%
“…Their existence in the auroral ionosphere has been securely established (e.g., Gumett et al, 1984;Dubinin et al, 1988;Boehm et al, 1990;Ishii et al, 1992). However, the transverse group velocity of short-scale SAWs, of interest, is rather high, constradicting the AS's stationarity.…”
Section: Introductionmentioning
confidence: 99%